2018
DOI: 10.1007/s11666-017-0683-x
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of Multilayered Suspension Plasma-Sprayed Thermal Barrier Coatings for Gas Turbine Applications

Abstract: Improvement in the performance of thermal barrier coatings (TBCs) is one of the key objectives for further development of gas turbine applications. The material most commonly used as TBC topcoat is yttriastabilized zirconia (YSZ). However, the usage of YSZ is limited by the operating temperature range which in turn restricts the engine efficiency. Materials such as pyrochlores, perovskites, rare earth garnets are suitable candidates which could replace YSZ as they exhibit lower thermal conductivity and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Lu et al and Smialek et al previously reported the critical TGO thickness at failure in TCF tested specimens to be approximately 7–8 µm [30,31,32]. The failed specimen does not show blue failure, indicating the presence of alumina in the failed region of TGO [33].…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al and Smialek et al previously reported the critical TGO thickness at failure in TCF tested specimens to be approximately 7–8 µm [30,31,32]. The failed specimen does not show blue failure, indicating the presence of alumina in the failed region of TGO [33].…”
Section: Resultsmentioning
confidence: 99%
“…The thermal barrier coating (TBC) is one of the best high temperature protective coatings at present, with the characteristics of heat insulation, corrosion resistance, wear resistance and erosion resistance, has been widely used in power machinery, aerospace and other high temperature and high heat flow environment [1,2]. During the service of TBC, defects such as cracking, debonding and even peeling of coatings are easy to occur, which will affect the operation safety and reliability of hot end components, and even have catastrophic consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing has been widely applied to biomaterial [14][15], aerospace [16][17][18], building [19,20] and so on. Recently, additive manufacturing technology brought revolution in gas turbine industry [21][22][23]. SIEMENS has finished its first full load engine tests for gas turbine blades produced using Additive Manufacturing technology in the early of 2017 [24].…”
Section: Introductionmentioning
confidence: 99%